O ADOLESCENTE E A HOSPITALIZAÇÃO - Maria Aparecida Tedeschi Cano; Christine Ranier Guzman (Universidade Federal de Goias, 2001)
Nursing is trying, in the last years, to develop researches about adolescence aiming to support teaching and assistance. In this study the object was the adolescent as in-patient and our goal was to know and to analyze his or her perception in relation to the nursing staff that was in charge to assist them and the interference provoked on his life by hospitalization. The methodology chosen is qualitative approach based in MINAYO (1996). The population studied was four adolescents , 14 to 17 years old, both sexes, in-patients of a n orthopedist unit of a third level hospital in Ribeirão Preto, SP. Semi-structured interview was the technique used to collect data; the main question was: "What do you think about hospitalization? (How is this experience for you)". The collected material was analyzed following the steps proposed by GOMES (1994) and the following study nuclei were identified: The adolescent in the hospital space and The health staff assisting the adolescent. In a general manner those nuclei showed preoccupation of the adolescents with their body images; dissatisfaction with the served food; ociosity; lack of recreation; discontent with older people in the same ward and the lack of acceptance by the health staff.